2022
DOI: 10.20517/cs.2022.26
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of the catalytic conversion of methanol to hydrocarbons

Abstract: For more than four decades, the methanol-to-hydrocarbons (MTH) reaction has been a successful route to producing valuable fuels and chemicals from non-petroleum feedstocks. This review provides the most comprehensive summary to date of recent research concerning the mechanistic fundamentals of this important reaction, covering different reaction stages. Mechanisms that have been proposed to explain the initial C-C bond formation during the induction stage of the MTH reaction are introduced, including the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 120 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…As the most abundant plant biomass resource, lignocellulosic biomass is recognized as the most promising renewable carbon feedstock for liquid fuels and chemicals production. Biomass-derived furanic compounds, such as furan, furfural, 2-methylfuran, and 5-hydroxymethylfurfural, are important platform molecules that can be obtained from lignocellulose and have attracted significant interest for aromatics production over acidic zeolite catalysts. In this process, furan undergoes a series of Diels–Alder condensation, decarbonylation, oligomerization, and alkylation reactions to form various olefins and aromatics comprising an active hydrocarbon pool (HCP) within zeolite channels. The HCP, originally proposed to explain methanol-to-hydrocarbon reactions, describes organics trapped in the zeolite scaffold that reactant molecules interact with, and products are released from a catalytic cycle. Similar HCP processes have been established for the transformation of methyl halides, methanethiol, biomass pyrolysis, light alkenes, and alkanes , into higher hydrocarbons. A recent study on the co-aromatization of furan and methanol over ZSM-5 zeolite found that furanic compounds can form highly proton-deficient intermediates as HCP species through dehydration or decarbonylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…As the most abundant plant biomass resource, lignocellulosic biomass is recognized as the most promising renewable carbon feedstock for liquid fuels and chemicals production. Biomass-derived furanic compounds, such as furan, furfural, 2-methylfuran, and 5-hydroxymethylfurfural, are important platform molecules that can be obtained from lignocellulose and have attracted significant interest for aromatics production over acidic zeolite catalysts. In this process, furan undergoes a series of Diels–Alder condensation, decarbonylation, oligomerization, and alkylation reactions to form various olefins and aromatics comprising an active hydrocarbon pool (HCP) within zeolite channels. The HCP, originally proposed to explain methanol-to-hydrocarbon reactions, describes organics trapped in the zeolite scaffold that reactant molecules interact with, and products are released from a catalytic cycle. Similar HCP processes have been established for the transformation of methyl halides, methanethiol, biomass pyrolysis, light alkenes, and alkanes , into higher hydrocarbons. A recent study on the co-aromatization of furan and methanol over ZSM-5 zeolite found that furanic compounds can form highly proton-deficient intermediates as HCP species through dehydration or decarbonylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[5][6][7][8] In recent years, there has been a remarkable surge of research in the field of CPL materials, with studies spanning various material categories such as supramolecular assemblies, liquid crystals, metal complex, and inorganic materials. [3,[9][10][11][12][13][14][15][16][17][18][19] For instance, supramolecular assemblies provide versatility and tunability through noncovalent interactions, allowing precise control over the molecular arrangement and CPL properties. [3,9,10] Liquid crystals, with their inherent selforganization and responsiveness to external stimuli, offer intriguing possibilities for achieving CPL through molecular alignment and ordering.…”
Section: Introductionmentioning
confidence: 99%
“…32 However, due to the difficulty of generating powder samples with reliable particle sizes and shapes, obtaining CPL results on solid-state samples that are reliable and artifact-free is challenging. 33,34 In this work, a polyvinylpyrrolidone-assisted (PVP-assisted) synthesis method was reported to fabricate crystalline and transparent thin films of optically active (10, 3)-a coordination polymers, [Ru(bpy) 3 ][Zn 2 (C 2 O 4 ) 3 ] for CPL measurements. The films displayed CPL signals with an enhanced g lum factor of 5 × 10 −3 compared to [Ru(bpy) 3 ] 2+ solutions.…”
mentioning
confidence: 99%